1995
DOI: 10.2214/ajr.164.1.7998542
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous ethanol injection for the treatment of hepatic tumors: indications, mechanism of action, technique, and efficacy.

Abstract: Percutaneous injection of ethanol for treatment of hepatic tumors was first described by Sugiura et al. [1] in 1983. To date, reported experience with the procedure has focused mainly on therapy of hepatoceilular carcinoma (HCC) [2-15], with little information available regarding its use in treating metastatic liver lesions [16]. Interest in this technique has grown recently as a possible means of treating patients with metastatic liver disease. The purpose of this perspective is to review the indications, mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…It is especially suitable for foci that could be clearly detected on ultrasound [29] . For the CT-guided PEI, it is a key step to insert the needle accurately into the target.…”
Section: Discussionmentioning
confidence: 99%
“…It is especially suitable for foci that could be clearly detected on ultrasound [29] . For the CT-guided PEI, it is a key step to insert the needle accurately into the target.…”
Section: Discussionmentioning
confidence: 99%
“…In experienced hands, the morbidity rate is low and quality of life is good. In addition to these drainage procedures, other treatment modalities were applied with some success for local elimination or inhibition of the tumour growth [6, 7]. However, the biological behavior of the HCC differs essentially from metastatic liver tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive jaundice due to mechanical tumour obstruction of the biliary tree, however, is only rarely caused by HCC. As for other hilar obstructions, there exist various possibilities for treatment: surgical excision in curative or palliative attempt, a variety of surgical biliodigestive bypass procedures [2, 3], interventional radiological [4]and endoscopical [5]insertion of an endoluminal prosthesis in order to bypass the obstruction, percutaneous injection of ethanol to reduce the size of the tumour [6, 7]and transcatheter arterial embolization (TAE) with different agents including radionuclide embolization with yttrium-90 [8, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Ethanol injection causes dehydration and intracellular coagulation, which leads to ne crosisand,ultimately,vascularocclusionand fibrosis. Recent studies showed that percuta neousethanolinjectiontherapyappearsto be effective for a limited number of small tu mors less than 3â€"S cm in diameter and that the 3-year survival rate with this therapy was similar to that of surgery [2]. We have treated large nodules with this procedure for the past 10 years, realizing it is important to insert multiple needles because ethanol may not diffuse evenly through large tumors, leaving some areas unaffected [3].…”
Section: Masatoshiimamura1mentioning
confidence: 98%